2005
DOI: 10.1037/0894-4105.19.6.739
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Visual Scanning as Predictors of Emotion Identification in Normal Aging.

Abstract: Emotion identification appears to decline with age, and deficient visual scanning may contribute to this effect. Eye movements of 20 older adults (OAs) and 20 younger adults (YAs) with normal saccades were recorded while viewing facial expressions. OAs made fewer fixations overall, and they made a higher proportion of fixations to the lower halves of faces. Topographical distribution of fixations predicted better OA accuracy for identifying disgust than other negative emotions. Impaired OA accuracy for fear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
186
10
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(232 citation statements)
references
References 46 publications
(78 reference statements)
26
186
10
3
Order By: Relevance
“…R 2 values indicated on each graph scan paths of the eyes and mouth may be unrelated to autism diagnosis, but instead are determined (in part) by the degree of co-morbid alexithymia in the sample of individuals with autism. Second, many studies have demonstrated the importance of typical scan paths in recognising facial emotion (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), therefore if alexithymia is associated with atypical scan paths to eyes and mouth, then the inconsistent findings with respect to recognition of emotional facial expression in autism (see Bal et al 2010;Jemel et al 2006) may also be explained by varying degrees of co-morbid alexithymia in the sample of individuals with autism across studies. We suggest therefore, that future studies of emotion processing in individuals with autism obtain measures of alexithymia in order to determine whether any impairments seen are due to autism, alexithymia, or the combination of these two factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…R 2 values indicated on each graph scan paths of the eyes and mouth may be unrelated to autism diagnosis, but instead are determined (in part) by the degree of co-morbid alexithymia in the sample of individuals with autism. Second, many studies have demonstrated the importance of typical scan paths in recognising facial emotion (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), therefore if alexithymia is associated with atypical scan paths to eyes and mouth, then the inconsistent findings with respect to recognition of emotional facial expression in autism (see Bal et al 2010;Jemel et al 2006) may also be explained by varying degrees of co-morbid alexithymia in the sample of individuals with autism across studies. We suggest therefore, that future studies of emotion processing in individuals with autism obtain measures of alexithymia in order to determine whether any impairments seen are due to autism, alexithymia, or the combination of these two factors.…”
Section: Discussionmentioning
confidence: 99%
“…As emotion recognition relies on appropriate fixation of the inner features of the face (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), the atypical visual scan paths exhibited by alexithymic individuals may therefore result in impaired recognition of emotion from facial expressions. These results support 'shared network' (Preston and de Waal 2002) accounts of social cognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations